2021
DOI: 10.1002/glia.23994
|View full text |Cite
|
Sign up to set email alerts
|

Implication of cerebral astrocytes in major depression: A review of fine neuroanatomical evidence in humans

Abstract: Postmortem investigations have implicated astrocytes in many neurological and psychiatric conditions. Multiple brain regions from individuals with major depressive disorder (MDD) have lower expression levels of astrocyte markers and lower densities of astrocytes labeled for these markers, suggesting a loss of astrocytes in this mental illness. This paper reviews the general properties of human astrocytes, the methods to study them, and the postmortem evidence for astrocyte pathology in MDD. When comparing astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 177 publications
(341 reference statements)
5
31
0
Order By: Relevance
“…In many NDDs, A1 astrocytes not only have potently neurotoxic effects, but they also amplify inflammatory microglial responses [ 14 , 17 , 56 ]. Several postmortem studies found that reduced astrocyte densities may be related to depressive episodes, and elevated astrocyte protein S100 beta in cerebrospinal fluid serum could be a biomarker of MDD [ 57 ]. Recently studies implied that appearance of A1 astrocytes is associated with depression-like behaviors induced by LPS and acute stress [ 20 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many NDDs, A1 astrocytes not only have potently neurotoxic effects, but they also amplify inflammatory microglial responses [ 14 , 17 , 56 ]. Several postmortem studies found that reduced astrocyte densities may be related to depressive episodes, and elevated astrocyte protein S100 beta in cerebrospinal fluid serum could be a biomarker of MDD [ 57 ]. Recently studies implied that appearance of A1 astrocytes is associated with depression-like behaviors induced by LPS and acute stress [ 20 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal studies MDD patients with higher baseline S100B levels exhibit a better response to antidepressant treatment. An elevated S100B level is detected not only in psychiatric conditions but also in many other neurological disorders such as traumatic brain injury, malignant melanoma, amyotrophic lateral sclerosis, and subarachnoid hemorrhage 17 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge, this is the first prospective study that tries to explore the correlation between S100B serum levels and mood disorders in adolescents and young patients. Based on the findings on glial pathology in mood disorders in adult patients 17 , 18 in our study, we provided some research questions following our hypothesis: (1) there are any differences in baseline serum S100B levels between depressed, hypomanic patients and healthy controls (2) could baseline S100B levels be influenced by clinical factors (severity of depressive and manic symptoms, medication status, family history of psychiatric and affective disorders, or gender) (3) is there a change between baseline S100B concentrations and euthymic state (as well as in a 2-year follow-up) and finally (4) do different baseline S100B levels predict diagnosis change from unipolar to bipolar disorder in young patients.…”
Section: Introductionmentioning
confidence: 99%
“…48 Similarly, the intermediate filament protein vimentin distinguishes stem cells in the developing and mature human and mouse V-SVZ, but can be expressed by other cell types outside the brain as well as parenchymal astrocytes. 61 Expression of the intermediate filament protein glial fibrillary acidic protein (GFAP) and the glutamate-aspartate transporter (GLAST) is also characteristic of V-SVZ stem cells, 38,62 reflective of their astrocyte-like properties. Within the V-SVZ, GFAP or GLAST expression distinguishes B-cells from their transit-amplifying and neuroblast progeny.…”
Section: Histochemical Features Of Neural Stem Cellsmentioning
confidence: 99%